Perilaku berisiko siswa di Kota Jambi - Yun Nina Ekawati; Nofrans Eka Saputra; Fadzlul Fadzlul; Jelpa Periantalo (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2017)
INTRODUCTION Risk behaviors are among student has been a problem in the field of health. The risk behavior including sexual behavior, smoking, drug abuse, bullying. METHOD This study aims to determine how many risk behaviors that had occured and other forms of risk behavior anything ever done by students. The study population was taken with purposive random sampling technique, the characteristics of which students (including smokers, active sexual behavior, drug users) aged 12-21 years. The sample of this research were 518 responden. Analysis of the data will be used using descriptive analysis. RESULTS The research findings show risk behavior has occurred in the school environment. Sexual behavior such as dating, holding hands, hugging, cheek and lips kissing, rubbing breasts and genitals, oral sex, sexual intercourse is a form existiong in student life. Resources porn more easily accessible for students, such as the internet, mobile phones/ gadgets, and peer group. Drug abuse and smoking occurs due to peer preasure. The elementary school is the first time students smoking and drug abuse. The incidence of risk behavior are more prevalent in the home and schools, because of the lack of parental supervision and the environment. CONCLUSIONS AND RECOMMENDATIONS Risk behavior has become a part of student life. Schools and government should work together to develop policies regarding the preparation of healthy school standard based physical and psychological dimensions. Keywords: Risk Behavior, Students